Kebijakan Dividen Di Bursa Efek Indonesiapada Perusahaan Kelompok LQ 45 - Sri Hasnawati (Jurnal Manajemen, 2017)
Dividend policy is very important in Finance Management. But until now the concept of dividend policy remains a debatable issue: should corporate profits be distributed or should they be kept as return earnings? In order to address the issue, research on public companies listed on the Indonesian stock exchange on LQ 45 companies is conducted. A model of multiple regression is used to explain what factors should be considered in carrying out the companyâ€™s dividend policy. The result of this study shows that main factors that should be considered in distributing the cash dividend are investment and leverage that may have an impact on the reduction of dividend. Size and liquidity variables do not affect dividend policy. When this study is related to agency theory, it seems that the companies in the LQ 45 have reduced agency conflict by increasing investment from internal and external sources. The creditors supplied external sources to increase managementÂ  control. The dividends were distributed in order to give a return on shareholders.